2000
DOI: 10.1590/s0036-46652000000200005
|View full text |Cite
|
Sign up to set email alerts
|

Malaria vectors in the Brazilian Amazon: Anopheles of the subgenus Nyssorhynchus

Abstract: SUMMARYVarious species of Anopheles (Nyssorhynchus) were studied in the Amazon with the objective of determining their importance as malaria vectors. Of the 33 known Anopheles species occurring in the Amazon, only 9 were found to be infected with Plasmodium. The different species of this subgenus varied both in diversity and density in the collection areas. The populations showed a tendency towards lower density and diversity in virgin forest than in areas modified by human intervention.The principal vector, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
206
0
14

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(236 citation statements)
references
References 15 publications
16
206
0
14
Order By: Relevance
“…Similar low infection indexes were found in previous studies in dry land areas and riverine rural areas of Rondônia (Gil et al 2003). In a recent review, Tadei and Dutary-Thatcher (2000) registered infection index of 0.2 to 2.0 for An. darlingi captured in various endemic areas of Brazilian Amazon, including sites close to those of the present study.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Similar low infection indexes were found in previous studies in dry land areas and riverine rural areas of Rondônia (Gil et al 2003). In a recent review, Tadei and Dutary-Thatcher (2000) registered infection index of 0.2 to 2.0 for An. darlingi captured in various endemic areas of Brazilian Amazon, including sites close to those of the present study.…”
Section: Discussionsupporting
confidence: 86%
“…An. darlingi is the main vector in all Amazon areas (Deane 1988, Lourenço-de-Oliveira 1988 Tadei & Dutary-Thatcher 2000) and it is the dominant species in both model areas (Gil et al 2003). However, while its favorable breeding sites are always large collections of water rich in aquatic vegetation and exposed to sun, they drastically differ in origin and development in different areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…darlingi bites/person/night in different geographical areas (Rubio-Palis 1995, Magris et al 2007, Moreno et al 2007). In Brazil, Tadei and Dutary-Thatcher (2000) reported biting rates that varied from 0.13-53, whereas Galardo et al (2007) reported much higher rates in AP, varying between villages from 53.9-837.7. The highest biting rate reported for An.…”
Section: Discussionmentioning
confidence: 98%
“…The level of malaria transmission is considered hypo-endemic. The main malaria vector in this area, as in most Amazon regions, is Anopheles darlingi, which is well known for its high vectorial capability (Tadei & Dutary 2000). There are two malaria laboratories providing diagnostic services and complete treatment for malaria 7 days a week.…”
Section: Study Design and Populationmentioning
confidence: 99%